Mode of action of T cells engineered with CAR or TCR for cancer treatment - Kobold, Sebastian (Henry Stewart Talks, 2026)
Genetically engineered T cells, T cell receptor modified T cells, Chimeric antigen receptor modified T cells, Anti-CD19 CAR T cell treatment, Tumor infiltrating lymphocytes